Variation in Tracheid Dimensions of Conifer Xylem Reveals Evidence of Adaptation to Environmental Conditions - Zheng, Jingming; Li, Yajin; Morris, Hugh; Vandelook, Filip; Jansen, Steven (Frontiers in Plant Science, 2022)
Globally distributed extant conifer species must adapt to various environmental conditions, which would be reflected in their xylem structure, especially in the tracheid characteristics of earlywood and latewood. With an anatomical trait dataset of 78 conifer tree species growing throughout China, an interspecific study within a phylogenetic context was conducted to quantify variance of tracheid dimensions and their response to climatic and soil conditions. There was a significant difference in tracheid diameter between early- and latewood while no significant difference was detected in tracheid wall thickness through a phylogenetically paired t-test. Through a phylogenetic principle component analysis, Pinaceae species were found to be strongly divergent in their tracheid structure in contrast to a conservative tracheid structure in species of Cupressaceae, Taxaceae and Podocarpaceae. Tracheid wall thickness decreased from high to low latitudes in both early- and latewood, with tracheid diameter decreasing for latewood only. According to the most parsimonious phylogenetic general least square models, environment and phylogeny together could explain about 21%~56% of tracheid structure variance. Our results provide insights into the effects of climate and soil on the xylem structure of conifer species thus furthering our understanding of the trees’ response to global change.